DIAGNOSIS CRITERIA FOR OCCUPATIONAL BRONCHITIS AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE ACCOMPANIED BY ARTERIAL HYPERTENSION - Kostyuk, І.F.; Kalmykov, О.; Byazrova, V.; Nagornaya, О.P. (World of Medicine and Biology, 2012)
102 males with dust pathology – workers of machine-building industry aged 52,3±4,71 years were examined. Arterial hypertension (AH) was diagnosed in 58 persons, dust bronchitis (DB) — in 25 patients, chronic obstructive pulmonary disease (COPD) of I stage in 28 persons (27,5 %), COPD of II stage - in 49 (48,0 %). DB and COPD on a background AH of characterised of more expressive clinical symptoms, frequent intensifying, greater rates of progressing.
Keywords: dust bronchitis; arteruial hypertension; clinic